Hydrothermal influence on barite precipitates in the basal Ediacaran Sete Lagoas cap dolostone, São Francisco Craton, central Brazil - Okubo, Juliana [UNESP]; Klyukin, Yury Igorevich; Warren, Lucas Veríssimo [UNESP]; Sublett, D. Matthew; Bodnar, Robert J.; Gill, Benjamin C.; Xiao, Shuhai (Elsevier, 2020)
Most Precambrian sediment-hosted barites have been interpreted to be diagenetic, hydrothermal exhalation, or methane-seepage in origin. Seafloor barite precipitates and void-filling barite cements in basal Ediacaran cap dolostones have been interpreted as sedimentary and early diagenetic in origin, and they have been used to infer ocean geochemistry in the aftermath of the terminal Cryogenian (or Marinoan) Snowball Earth glaciation. Barite crystals precipitated syndepositionally from seawater or authigenically from marine porewaters can potentially offer insights into Neoproterozoic ocean geochemistry. In this study, we analyzed void-filling barite cements from the basal Ediacaran Sete Lagoas cap dolostone to determine whether the barite records seawater geochemical signatures and whether it experienced post-depositional hydrothermal alteration. Sete Lagoas barite occurs as veins and major void-filling cement in multiple horizons, sometimes interbedded with carbonate fans. Barite crystals, commonly forming rosettes, grew upwards and downwards as radiating bladed crystals, isolated crystals in the matrix, and inclusions within carbonate fan crystals. Sulfur isotope compositions of coexisting barite and carbonate-associated sulfate (CAS) show similar values, suggesting a similar sulfate source, potentially seawater sulfate from a shallow marine environment. Assuming that CAS was sourced from seawater sulfate, we infer that the Sete Lagoas barite was precipitated from marine porewaters with seawater as a source of the sulfate. Carbonaceous material (CM) and fluid inclusions in barite crystals share a similar thermal history with a peak temperature in the range of 206–257 °C. CM was not detected in the host rock, possibly due to pervasive dolomitization, thermodegradation of CM or the fine-grained nature of the host rock. Estimated temperatures and salinity based on fluid inclusions are both higher than seawater, suggesting that hydrothermal activity, perhaps those related to Mississippi-Valley type mineralization in the São Francisco Craton, may have influenced the Sete Lagoas barite. Thus, although the Sete Lagoas barite may have originally precipitated from seawater or marine porewaters in communication with seawater, it may have been subsequently influenced by hydrothermal activity and therefore a more thorough diagenetic assessment must be done before the Sete Lagoas barites can be used to infer seawater geochemistry and environment in the aftermath of Marinoan Snowball Earth.